Occurrence and serotype distribution of Aggregatibacter actinomycetemcomitans in subjects without periodontitis in Turkey - Doğan, Başak; Chen, Jason; Çiftlikli, Sinem Yıldız; Huang, Jonathan; Kadir, Tanju; Alnıak, Anıl Kınacı; Chen, Casey (Archives of oral biology, 2016)
To determine the occurrence and serotype distribution of Aggregatibacter actinomycetemcomitans in subjects without periodontitis. Systemically healthy dental students without periodontitis (n=94), who had not used antibiotics within the last 3 months or received any form of periodontal therapy within the last 6 months, were included in the study. Pooled subgingival microbiological samples were collected from 4 first molars and 4 central incisors in each subject using sterile paper points. All samples were tested for the presence and the serotype of A. actinomycetemcomitans through PCR analysis of the 16S rRNA genes and the serotype-specific gene clusters in the DNA extracted from the samples. Of the 94 samples that were tested, 43 (46%) were positive for A. actinomycetemcomitans. No statistically significant differences in clinical parameters were found between subgingival sites with or without detectable A. actinomycetemcomitans (t-test, P>0.01). Among the 43 A. actinomycetemcomitans-positive samples, the serotype was identified in 21 samples. Fifteen were positive for A. actinomycetemcomitans serotype a, 1 for serotype b, 1 for serotype c, and 4 for serotype f, while serotypes d and e were not detected. A. actinomycetemcomitans serotype a is the most commonly found serotype among Turkish dental students without periodontitis.